P0514USP30 INHIBITOR ATTENUATES PROGRESSIVE FIBROSIS IN ISCHEMIA INDUCED CHRONIC KIDNEY DISEASE (CKD), EVEN AFTER DELAYED TREATMENT INITIATION AFTER INJURY. (6th June 2020) - Bedford, David; Wright, Jamie; Rong, Song; Thompson, Paul; Shushakova, Nelli; Schmidt, Sonja; Gueler, Faikah; Molnar, Judit
Abstract: Background and Aims: Much literature evidence points towards an essential role of mitochondrial quality control mechanisms in acute kidney injury progression. Renal ischemic-reperfusion injury (IRI) results in metabolic adaptation of proximal tubule epithelial cells, a site of high mitochondrial turnover (1). Moreover, exacerbation of renal injury has been demonstrated following IRI in both PTEN-induced kinase 1 (PINK1) knockout and Parkin knockout mice (2). The identification of a single point mutation (m.547A>T) within the mitochondrial genome of a large pedigree of patients with maternally-inherited tubulointerstitial kidney disease, highlights the importance of mitochondrial integrity in human renal pathophysiology (3). USP30 is a mitochondrial associated deubiquitylating enzyme that acts on the mitochondrial import receptor subunit TOM20 to repress PINK1/Parkin-mediated mitophagy and modulate mitochondrial protein transport (4, 5). Within kidney, USP30 expression is predominantly tubular and accordingly, USP30 inhibition may provide a mechanism to protect against IRI. MTX008 is a selective small molecule inhibitor of USP30. Prophylactic administration of MTX008 15 mg/kg (p.o.) BID has shown robust and reproducible efficacy in a mouse model of IRI-induced kidney fibrosis (6). Here we present data showing that dosing MTX008 15 mg/kg (p.o.) BID in a therapeutic paradigm, also results in efficacy in the same IRI-induced kidney fibrosis model. Method: On Day 0 (zero) C57BL/6 mice were anaesthetized, and their left renal pedicle was clamped transiently for 45 min, causing circulatory arrest in the kidney with consecutive IRI. Mice were then administered either vehicle or MTX008 15 mg/kg (p.o.) BID for 21 days, with first treatment starting five hours following IRI surgery (i.e. therapeutics dosing). Mice were monitored and kidneys harvested at Day +21. Kidney sections were quantitatively assessed for relative cellular morphology, fibrosis and macrophage infiltration using blinded histological scoring methods. Results: Body weight was similar between groups and remained constant throughout the observation periods. Masson trichrome staining revealed significantly less tubular atrophy in MTX008 treated animals on Day +21. Similarly, fibronectin expression and macrophage infiltration in the cortex was also significantly reduced in MTX008 treated mice on Day +21. Conclusion: MTX008, a novel selective small molecule inhibitor of USP30 has shown efficacy in a model of IR-induced CKD when dosed therapeutically. Initiating treatment after the establishment of IRI has shown significant benefits towards reduced progression to CKD with less tubular atrophy and renal fibrosis. Mission Therapeutics is investigating MTX008 in a variety of preclinical renal injury models with a view to developing this novel molecule towards the clinic. Therapeutic dosing opens a new and attractive opportunity for the treatment of AKI and sets our UPS30 inhibitor apart from other molecules currently in development.